Der Futurismus : Manifeste und Dokumente einer künstlerischen Revolution 1909-1918 - Apollonio, Umbro (Köln : Verlag M. DuMont Schauberg, 1972)
Carrà, Carlo Dalmazzo ; Boccioni, Umberto ; Severini, Gino ; Balla, Giacomo ; Marinetti, Emilio ; Picasso, Pablo ; Prampolini, Enrico ; etc.
Duits
boek